THE RECONSTRUCTION OF POLICY RELATED TO THE OPTIMISATION ON NATIONAL SOCIAL SECURITY PUBLIC MEMBERSHIP - Nabitatus Sa'adah (Diponegoro Law Review, 2020)
One of the people’s needs in terms of effort to manifest the purpose of the state which is to establish national well-being is by providing social security. Social security is a form of social protection to meet citizens' basic needs. Associated with the implementation of national social security, the government obligates its citizens to participate in the program. However, the fact was there are still many citizens which are reluctantly participating in the program. It is leading to funding collection to be not optimal and affecting the implementation of social security. The research is adopting normative approach, which is stressed on the secondary data. The research specification is an analytic description with qualitative analysis. The national social security is a compulsory program for all of the Indonesian citizens particularly for the independent level, however, not all have joined it particularly self-referred participants. Several aspects causing this problematic program, such as the lack of people's awareness. The lack of people discipline toward the payment, ineffective sanctions and lack of service, are proved with the abundant number of payment arrears by independent participants. The reconstruction of optimization of National Social Security Program is managed with the improvement of legal substance, legal structure and legal culture.